Kultura śródziemnomorska jako uniwersalna cywilizacja zachodnia. Dociekania filozoficzno-literackie - Klimczak, Dariusz Piotr (Colloquia Litteraria, 2022)
The Author asks whether the Mediterranean culture developed a higher civilization, explicitly a European universal civilization? He tries to answer for this question having at his disposal various philosophical views, historical facts, thesis of culturologists and sociologists, often referring to the literary contexts and exemplification. In this work, the thesis that „Every civilization is a culture, but not every culture is also a civilization” has been reversed. The transition from the culture to the civilization is close to the thesis of V.S. Naipaul, who noticed, that in the 20th century a universal civilization was created, which concerns the cultural unification of humanity and the increasingly common acceptance of the common values, beliefs and customs. Analyzing the spirit of the Mediterranean civilization, the authortries to explains that it is the Western civilization, and with his rich inventory of notions of symbols, ideas, phenomenas, and creating the universal reservoir and „the pattern for the future” constantly immersed in the ancient past. Also climate – philosophy – literature – religion and politics – the idea of Living Thought), created the basic determinant of the Western civilization. Moreover, when recording the durability of logos, individualism, „circular” and pax romana lists the features of the Mediterranean culture, considering anthropocentrism and individualism as the main dominant feature.